Effect of Increasing L-Lysine-HCl and Amino Acid Ratios on Performance of Finishing Pigs From 240 to 285 lb - Larissa L. Becker; Mike D. Tokach; Robert D. Goodband; Joel M DeRouchey; Jason C. Woodworth; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 1,789 pigs (337 × 1050, PIC; initial BW 240.0 ± 2.51 lb) were used to determine the effects of increasing L-Lys-HCl and AA ratios on performance of late finishing pigs fed diets without DDGS. The study used 2 groups of pigs and each study lasted 18 and 27 d, respectively. Pigs were housed in mixed gender pens with 20 to 25 pigs per pen and 19 replications per treatment (10 and 9 replications per group, respectively). Pens of pigs were blocked by BW and randomly allotted to 1 of 4 dietary treatments. Treatment diets consisted of low, medium, or high levels of feed-grade AA and moderate or high AA ratios relative to Lys. Medium and high levels of feed-grade AA treatments had increased L-Lys-HCl in replacement of soybean meal to achieve CP levels of 12.0, 11.0, and 11.1%. The AA ratios were increased in the low CP diet to achieve a minimum of 60% Ile, 128% Leu, 36% Met, 70% Thr, 21.2% Trp, 72% Val, and 33% His for the high AA ratio treatment. Overall, there was a marginally significant increase in ADFI (quadratic,P= 0.097), with the greatest response observed in pigs fed medium feed-grade AA and moderate AA ratios. Treatment diets had no effect on ADG or F/G. At the end of study 2, carcass data were collected and analyzed. No differences (P>0.10) were observed for HCW, carcass yield, backfat depth, loin depth or percentage lean. In summary, differing levels of feed-grade AA and AA ratios did not impact growth performance or carcass characteristics with the exception of a marginally significant (quadratic,P= 0.097) increase in ADFI.
Keywords: lysine; amino acids; finishing pig